METODE PENDIDIKAN ANAK DALAM KELUARGA MENURUT ABDULLAH NASHIH ULWAN DAN RELEVANSINYA DENGAN PENDIDIKAN ANAK DALAM KELUARGA DI KELURAHAN MAJAPAHIT KOTA LUBUKLINGGAU - Adi Sutrisno (IAIN Bengkulu, 2017)
This study aims to describe the method of education of children in the fami-ly according to the concept of ‘ Abd Tarbiyatul Nashih Ulwan in Awlad fil Islam and describe the relevance of the method of education of children in the family according to the concept of ‘ Abd Tarbiyatul Nashih Ulwan in Awlad fil Islam with education in Neighborhoods of Majapahit city of Lubuklinggau. This study uses descriptive qualitative approach. In obtaining the data, the authors use tech-niques of observation, interviews, a list of the checklist, and documentation. From the results of this research were obtained results that: child education Methods in the family according to the concept of ‘ Abd Tarbiyatul Nashih Ulwan in Awlad fil Islam, namely, first, the educational method with the example. Se-cond, education with indigenous customs. Third, education with advice. Fourthly, the education by providing oversight. Fifth, education by giving away penalties. The fifth method of education are the most important methods for achieving the goal of education is the morals of the child. Child education methods with example parents according to Abdullah Nashih Ulwan still relevant applied in Kelurahan Majapahit City Lubuklinggau, among them the example of parents in adopting good example, in generosity, ex-ample parents in avoiding bad morals. Child education methods with customs ac-cording to Abdullah Nashih Ulwan still relevant applied in district Majapahit city of Lubuklinggau. Method of education with advices according to Abdullah Nashih Ulwan still relevant applied in Kelurahan Majapahit city of Lubuklinggau. Method of educa-tion of a child with attention according to Abdullah Nashih Ulwan still relevant applied in district Majapahit City Lubuklinggau, as parents pay attention to or su-pervise the conditions of the faith of children, pay attention to the moral and be-havior of the child, and pay attention to the implementation of the children’s wor-ship. Methods of education by providing punishment according to Abdullah Nashih Ulwan still relevant applied in district Majapahit City Lubuklinggau, if teaching, advice and oversight are not followed by the son, then the final path is giving the punishment on a child that aim to educate